2017
DOI: 10.2174/1573406413666170209124302
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method to Predict Blood-Brain Barrier Permeability of Drug- Like Compounds Using Classification Trees

Abstract: Finally, we can say that, the present model would be a valuable tool in the early stages of drug discovery process of neuropharmaceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…The fpr values behaved below the 12% threshold [LDA (α‐amylase): 3.67% training, 9.17% cross‐validation, and 11.82% for the test sets] and for the case of LDA (α‐glucosidase): 2.73% training, 11.82% cross‐validation, and 10.88% test sets. Although these values are higher than the previous case, they keep below 15%, which is also recommended (Castillo‐Garit, Casanola‐Martin, Le‐Thi‐Thu, Pham‐The, & Barigye, ).…”
Section: Resultsmentioning
confidence: 88%
“…The fpr values behaved below the 12% threshold [LDA (α‐amylase): 3.67% training, 9.17% cross‐validation, and 11.82% for the test sets] and for the case of LDA (α‐glucosidase): 2.73% training, 11.82% cross‐validation, and 10.88% test sets. Although these values are higher than the previous case, they keep below 15%, which is also recommended (Castillo‐Garit, Casanola‐Martin, Le‐Thi‐Thu, Pham‐The, & Barigye, ).…”
Section: Resultsmentioning
confidence: 88%
“…Additionally, based on 3PRule and models developed by Pham‐The et al ., all compounds were classified as moderate permeability with P app values ranged from 2.8 to 7.2 × 10 −6 cm/s. Using the BOILED‐Egg approach in consensus with our recent methods, all compounds were estimated as having high gastrointestinal (GI) absorption and good ability to permeant through Blood‐Brain Barrier (BBB). However, 4b , 4c , and 4g were identified as potential P‐glycoprotein substrate .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, this descriptor appeared in the best four RF models created in [5] using up to four descriptors. Moreover, PSA was used in a classi cation tree model [7] as the criterion allowing the rst split of the tree. In addition, D. Zhang et al [11] listed PSA among the ten most signi cant descriptors.…”
Section: Discussionmentioning
confidence: 99%
“…While such models assign speci c logBB/PR values for each drug, binary models have so far reached a higher prediction accuracy and provide a preliminary insight regarding the behavior of candidate drugs which is su cient in early drug discovery stages. Predominantly, binarization of drug permeability across the BBB is performed by setting empirical thresholds to logBB values [5][6][7][8][9]. However, S. Kunwittaya et al [6] have shown that varying logBB thresholds lead to a difference in the prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation